2013
DOI: 10.1007/s13209-013-0101-7
|View full text |Cite
|
Sign up to set email alerts
|

Immigration and student achievement in Spain: evidence from PISA

Abstract: This paper provides the first evidence on the dynamics of immigrant students' achievement following their migration to Spain. Using the data from 2003, 2006 and 2009 wave of the Programme for International Student Assessment (PISA), we show that immigrant students tend to perform significantly worse than native students, but that their performance improves with time spent in Spain. Among immigrants, Latin Americans enjoy an initial linguistic advantage, which, however, does not help them to catch up faster. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
26
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 19 publications
5
26
0
9
Order By: Relevance
“…3 below). This considerable gap in performance between the immigrant and the native-born students, particularly, Latinos, in some provinces of Spain broadens more than 50% of the standard deviations of the scores (Etxeberría & Elosegui, 2010;Fernández-Enguita, Mena & Riviere, 2010;Vaquera & Kao, 2012;Zinovyeva et al, 2008). In line with these findings another study indicated that in Spain as in most countries of the OECD, schools with large concentrations of immigrants have the worst performance, suggesting that in these schools the whole student body gets affected (Cebolla-Boado & Garrido-Medina, 2008).…”
Section: Ipv and Child Maltreatment In The Context Of Immigrationmentioning
confidence: 99%
See 1 more Smart Citation
“…3 below). This considerable gap in performance between the immigrant and the native-born students, particularly, Latinos, in some provinces of Spain broadens more than 50% of the standard deviations of the scores (Etxeberría & Elosegui, 2010;Fernández-Enguita, Mena & Riviere, 2010;Vaquera & Kao, 2012;Zinovyeva et al, 2008). In line with these findings another study indicated that in Spain as in most countries of the OECD, schools with large concentrations of immigrants have the worst performance, suggesting that in these schools the whole student body gets affected (Cebolla-Boado & Garrido-Medina, 2008).…”
Section: Ipv and Child Maltreatment In The Context Of Immigrationmentioning
confidence: 99%
“…Given the constant flow of immigrant students into most developed countries, accompanied by a pervasive academic underachievement (Cebolla-Boado & Garrido-Medina, 2008;Vaquera & Kao, 2012;Zinovyeva, Felgueroso, & Vázquez, 2008), it is substantive the identification of risk factors that compromise students' cognition and school performance.…”
Section: Introductionmentioning
confidence: 99%
“…5 Pese a que PISA no mide el rendimiento de los alumnos en sí mismo, sino la capacidad académica demostrada en una serie de pruebas estandarizadas, la correlación entre los resultados de esta prueba y los que los alumnos obtienen en sus respectivos centros es elevada, puesto que lo que mide son competencias por las que el alumnado también es evaluado. De sus datos de 2006 pueden encontrarse evidencias de la desventaja de los estudiantes de origen inmigrante en España en Cebolla (2009), Salinas y Santín (2012, y en Zinovyeva et al (2013), entre otros. 6 Véase, por ejemplo, Salinas y Santín (2012) y Zinovyeva et al (2013).…”
unclassified
“…De sus datos de 2006 pueden encontrarse evidencias de la desventaja de los estudiantes de origen inmigrante en España en Cebolla (2009), Salinas y Santín (2012, y en Zinovyeva et al (2013), entre otros. 6 Véase, por ejemplo, Salinas y Santín (2012) y Zinovyeva et al (2013). 7 Véase, por ejemplo, OECD (2009: 281).…”
unclassified
See 1 more Smart Citation